Prevention and rehabilitation of muscle hypotonicity of vertebrogenic origin during preparation for the main competitions of the season - Ilyin, A. B.; Cherkasov, A. D.; Ivkov, A. N.; Morozov, V. I. (Theory and Practice of Physical Culture, 2023)
Objective of the study was to develop a methodology for testing the muscular system of athletes and special regular physical exercises as a method of preventing muscle hypotonicity in the biomechanical parts of the muscular topography of athletes, built into the structure of training sessions.